Functional magnetic resonance imaging (fMRI) in design studies: Methodological considerations, challenges, and recommendations. (January 2022) - Hay, L.; Duffy, A.H.B.; Gilbert, S.J.; Grealy, M.A.
Abstract : Functional magnetic resonance imaging (fMRI) enables identification of the brain regions and networks underpinning cognitive tasks. It has the potential to significantly advance cognitive design science, but is challenging to apply in design studies and methodological guidance for design researchers is lacking. In this Research Note, we reflect on our experiences and other work to outline the activities involved in developing and executing fMRI design studies. The implications for research quality at each stage are highlighted. We then consider the challenges for fMRI research on design and make recommendations for addressing them. Four critical areas are identified: establishing experimental protocols; establishing a cognitive design ontology; generating foundational knowledge about brain activation; and balancing fMRI constraints against ecological validity. Highlights: Methodological guidance on fMRI for design researchers is lacking. We outline the activities involved in developing and executing fMRI design studies. Methodological and conceptual decisions have implications for fMRI results quality. Protocols, ontology, and foundation knowledge need developed for fMRI design studies. Balancing fMRI constraints and ecological validity is also a key challenge.